2015
DOI: 10.5539/ies.v8n4p122
|View full text |Cite
|
Sign up to set email alerts
|

Matching University Graduates’ Competences with Employers’ Needs in Taiwan

Abstract: The dramatic expansion of the number of higher educational institutions in Taiwan has contributed a great deal to the growing unemployment rate of university graduates. Given the accumulated number of students who graduated in previous years and failed to find a job, the pressure of finding a job is growing each year. On the other hand, however, many employers lamented that they are struggling to find qualified job candidates. The major reason for this mismatch is that the traditional university instruction th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Immediate supervisors in Quality Assurance units experience personal qualities as the most important and are the priorities of both employability skills that must be acquired by prospective graduates before entering the workplace in the Research and Development unit, Maintenance unit and Production unit. This finding is in line with the results of the study conducted by Ho (2015) where the employer puts a dimension of personality that includes loyalty and ethics followed by disciplined and has the best preferences. This finding is similar to the findings of Latisha and Surina (2010) that employers are looking for employees with high personal qualities.…”
Section: The Importance Of Employability Skills Applicationsupporting
confidence: 90%
“…Immediate supervisors in Quality Assurance units experience personal qualities as the most important and are the priorities of both employability skills that must be acquired by prospective graduates before entering the workplace in the Research and Development unit, Maintenance unit and Production unit. This finding is in line with the results of the study conducted by Ho (2015) where the employer puts a dimension of personality that includes loyalty and ethics followed by disciplined and has the best preferences. This finding is similar to the findings of Latisha and Surina (2010) that employers are looking for employees with high personal qualities.…”
Section: The Importance Of Employability Skills Applicationsupporting
confidence: 90%
“…Majority of those who acquired their master's degree are graduates from the College of Education since the graduate courses are offered in the said location. The respondents of a tracer study also came from different academic majors such that 27% majored in agriculture, 27% in education and social sciences, 20% in construction and engineering, and 26% in business (Ho, 2015). Evidence from surveys stated that career-specific and generalist degrees can produce employability outcomes among the graduates (Kinash et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…If the need for relevance in the curriculum is not met, graduates are then prompted to take a lengthy transition from the university to the labor market which leads to a long time looking for an appropriate job that matches their qualifications (Ho, 2015). The learning competencies are a loss on investment when graduates are unable to fit the degree, interests, and capabilities developed at a university to the demands of the labor market (Corominas, Saurina, & Villar, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The technical and technological skills required depend on the type of organisation. Employees should possess job-specific knowledge and skills (Ho, 2015) and be able to apply subject knowledge (Messum et al, 2011;Mirza et al, 2014). These findings concur with Husain et al (2010), who found that personal qualities, thinking and interpersonal skills showed no significant difference by type of organisation, but that information and technological skill requirements do.…”
Section: Discussionmentioning
confidence: 99%